Konsep Business Agility Untuk Peningkatan Pendapatan Non Aeronautical Di Bandar Udara Adi Soemarmo Boyolali - Sudur, Misbah; Ubaedillah, Ubaedillah; Sonhaji , Imam (Green Publisher Indonesia, 2025)
This study aims to determine the success factors in implementing the Business Agility concept and the Business Agility marketing strategy carried out whether it affects the addition of airport revenue through the Non Aeronautical side. The method used in this study uses a qualitative method to provide innovation in the application of the Business Agility concept at Adi Soemarmo Boyolali Airport. The results showed that the Business Agility concept to increase airport revenue through the Non Aeronautical side by organizing events that are in accordance with the conditions of the local community and collaborating between the airport management with Micro, Small and Medium Enterprises (MSMEs) and the community through the Non Aeronautical side and efforts to increase customer satisfaction and interest in air transportation services, as well as several other benefits. Having an appropriate and effective marketing strategy is a step or way to create an Event for service users at the airport in an effort to increase Non Aeronautical revenue.